2021
DOI: 10.3390/foods10092222
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Soy Protein Prepared Using an Aqueous Ethanol Washing Process

Abstract: Currently, the predominant process for soy protein concentrate (SPC) production is aqueous ethanol washing of hexane-extracted soy meal. However, the use of hexane is less desired, which explains the increased interest in cold pressing for oil removal. In this study, cold-pressed soy meal was used as the starting material, and a range of water/ethanol ratios was applied for the washing process to produce SPCs. Washing enriched the protein content for the SPCs, regardless of the solvent used. However, we conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
0
15
1
Order By: Relevance
“…On the other hand, some differences in the microstructures were observed in the kernel residues after hexane and 80% ethanol extraction. In a comparison to Gd-k1 and Gl-k1, the images of the Gd-r1 and Gl-r1 appeared to be more separated and with large chunks disrupting the outer layer of the fibers, similar to the microstructures of those defatted cottonseed and soy meal products [ 64 , 65 ]. Thus, we attributed this micromorphological difference to the oil component.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, some differences in the microstructures were observed in the kernel residues after hexane and 80% ethanol extraction. In a comparison to Gd-k1 and Gl-k1, the images of the Gd-r1 and Gl-r1 appeared to be more separated and with large chunks disrupting the outer layer of the fibers, similar to the microstructures of those defatted cottonseed and soy meal products [ 64 , 65 ]. Thus, we attributed this micromorphological difference to the oil component.…”
Section: Resultsmentioning
confidence: 99%
“…The main soy protein constituents in the control were visible in both the P0 and P1 phases, as shown in Figure 4 a. Based on their estimated molecular masses of 83.4, 74.6, 49.0, 39.7, 35.6, and 20.1 kDa, respectively, these constituents were hypothesized to be the 7S α′, 7S α, and 7S β subunits (bands numbered as 1, 2, and 3, respectively), 11S A3 subunit (band numbered as 4), 11S acidic subunits (bands numbered as 5), and 11S basic subunits (bands numbered as 6) [ 35 ]. In contrast, all these bands were reduced in the P1 stage compared to the P0 stage because of the dilution effect of the simulated saliva.…”
Section: Resultsmentioning
confidence: 99%
“…In the study of Wang et al (55), higher recoveries of soy protein concentrates were obtained when it was produced from extruded-expelled soybean meals by using acid and alcohol wash methods (over 78% yield and more than 95% protein recovery). Peng et al (31) also observed that using water alone as a solvent in the washing process resulted in the lowest yield (around 45%) and protein (approximately 50%) recovery, increasing the concentration of ethanol in the solvent up to 80% increased the yield and protein recovery to almost 81 and 90%, respectively. As indicated by Luthria et al, (56), particle size, the pre-treatment method applied to raw materials, the solid-liquid ratio during the solvent-washing process, and the solidliquid separation method also have an impact on SPC production and protein yields.…”
Section: Evaluation Of the Low-resource Spc Methods On Large-scale Pr...mentioning
confidence: 98%